2022
DOI: 10.1155/2022/1832241
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Mechanism of Afuresertib against Esophageal Cancer

Abstract: Esophageal cancer (EC) is a common malignant tumor of the digestive system. Exploring the molecular biological mechanism of EC will help to clarify its carcinogenesis mechanism, find important molecular targets in the process of carcinogenesis, and provide new ideas for the diagnosis and treatment of EC. Phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt) signaling pathway is one of the signal transduction pathways most closely related to cell proliferation and apoptosis. The regulation of various down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As a new inhibitor of AKT signal pathway, Afuresertib can be used to treat a variety of tumors. Studies in esophageal cancer have found that Afuresertib antagonizes tumor progression mainly by inhibiting the expression of PI3K and Akt pathway proteins [45].…”
Section: Discussionmentioning
confidence: 99%
“…As a new inhibitor of AKT signal pathway, Afuresertib can be used to treat a variety of tumors. Studies in esophageal cancer have found that Afuresertib antagonizes tumor progression mainly by inhibiting the expression of PI3K and Akt pathway proteins [45].…”
Section: Discussionmentioning
confidence: 99%
“…Afuresertib is an Akt pathway inhibitor that exerts cytotoxic and antiproliferative activities in human cancer cells ( Uko et al, 2020 ). And in the study in rats, it was also found that Afuresertib can inhibit the expression of PI3K and Akt-related proteins in rat tumor tissues to exert its anti-tumor effect ( Min et al, 2022 ). These show that Afuresertib has anti-tumor effects in both humans and animals.…”
Section: Discussionmentioning
confidence: 99%